Minyak Urapan dalam Perspektif Alkitab dan Relevansinya pada Masa Kini - Ayub Sugiharto (Sekolah Tinggi Alkitab Batu, Malang, 2024)
The polemic of using anointing oil is still an interesting topic of conversation today. There has been much discussion and argumentation about the use of a certain